(3Gdhge hGdEjgGe GdhGbYjf aj cJGH GdCMcGes - (3Ydj Hf eMeO Hf YHO Gdedc GdcJGej GdMejQj GdaGSj, CHh GdMSf GHf GdbWGf , J (B628 (3g` s; (3YHO GdMb Hf YHO GdQMef Hf YHO Gddg GdCROj GdETHjdj, CHh eMeO, GdeYQha H` GHf GdNQGW,J (B581 (3g` s
(3ChdgG (B:s
(3hHYO aEf CHG eMeO YHO GdMb Hf YHO GdQMef GdCROi Ke GdETHjdi QMeI Gddg Ydjg bO NdO ai cJGHg GdPi LeY ajg CMGOjK CaYGd Gdecdajf s
(3BNQgG (B:s
(3EdG CHG eMeO YHO Gddg Hf eMeO aEffi dG CYQag hEfeG cJHJg hGddg Gdehab s
(3GdfSNI HgG MhGTs
(3HgG ebGHdI Ydi GdCUd Gdefbhdg efg ai BNQgGs
(3fSNI KGfjI s
(3JHUQI GdYfhGf (B:s
(3GSJOQGcs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs